2021
DOI: 10.1186/s12874-021-01329-3
|View full text |Cite
|
Sign up to set email alerts
|

The INSPIRE Population Survey: development, dissemination and respondent characteristics

Abstract: Background Most older adults prefer to continue living at home despite increasing care needs and demand for services. To aid in maintaining independence, integrated care models for community-dwelling older people are promoted as the most cost-effective approach. The implementation of such care models is challenging and often the end-users are not involved or their needs are not considered. We conducted a population survey in order to understand the needs and preferences of home-dwelling older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 26 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…1) [41]. First, we conducted secondary analysis on a subset of data from the cross-sectional INSPIRE population survey [39] (which was part of the parent study). To help explain and expand on these results [41], we used data from interviews with older adults in the INSPIRE parent study [40] (which used Interpretive Description [42]).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1) [41]. First, we conducted secondary analysis on a subset of data from the cross-sectional INSPIRE population survey [39] (which was part of the parent study). To help explain and expand on these results [41], we used data from interviews with older adults in the INSPIRE parent study [40] (which used Interpretive Description [42]).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the INSPIRE population survey in the parent study [39], selected socio-demographic variables were descriptively analysed and reported as frequencies, percentages, medians, and interquartile range (IQR) to describe the sample of survey participants. We also included a description of household members to support interpretation of care use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations